COVID-19 mortality rate in nine high-income metropolitan regions - Signorelli, Carlo; Odone, Anna; Gianfredi, Vincenza; Bossi, Eleonora; Bucci, Daria; Oradini-Alacreu, Aurea; Frascella, Beatrice; Capraro, Michele; Chiappa, Federica; Blandi, Lorenzo; Ciceri, Fabio (Acta Biomedica Atenei Parmensis, 2020)
We analyzed the spread of the COVID-19 epidemic in 9 metropolitan regions of the world with similar socio-demographic characteristics, daytime commuting population and business activities: the New York State, Bruxelles-Capital, the Community of Madrid, Catalonia, the Île-de-France Region, the Greater London county, Stockholms län, Hovedstaden (Copenhagen) and the Lombardy Region. The Lombardy region reported the highest COVID-19 crude mortality rate (141.0 x 100,000) 70-days after the onset of the epidemic, followed by the Community of Madrid (132.8 x 100,000) New York State (120.7 x 100,000). The large variation in COVID-19 mortality and case-fatality rates for COVID-19 in different age strata suggested a more accurate analysis and interpretation of the epidemic dynamics after standardization of the rates by age. The share of elder populations (>70 years) over total population varies widely in the considered study settings, ranging from 6.9% in Catalonia to 17.0% in Lombardy. When taking age distribution into consideration the highest standardized mortality rate was observed in the State of New York (257.9 x 100,000); with figures in most of the European regions concentrated between 123.3 x 100,000 in Greater London and 177.7 x 100,000 in Bruxelles-Capital, lower in French and Danish regions. We also report and critical appraise, when available, COVID-19 mortality figures in capital cities, nursing homes, as well as excess mortality at country level. Our data raise awareness on the need for a more in-depth epidemiological analysis of the current COVID-19 public health emergency that further explores COVID-19 mortality determinants associated with health services delivery, community-level healthcare, testing approaches and characteristics of surveillance systems, including classification of COVID-19 deaths.